Pengaruh Penerapan Good Corporate Governance (GCG) Terhadap Nilai Perusahaan Dan Kinerja Keuangan Perusahaan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Refsi Abraar; Wita Dwika Listihana; Rinayanti Rasyad (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The purpose of the study was to determine the effect of the implementation of Good Corporate Governance on Firm Value and Financial Performance. The sampling used purposive sampling technique, namely the selection of samples with certain criteria, so that the sample in this study was 32 samples. The implementation of Good Corporate Governance was measured by a score of corporate governance perception. index (CGPI). Firm value is measured by Tobin's q and financial performance is measured by return on assets (ROA). The results show that there is a significant negative relationship between good corporate governance and firm value, and there is a significant negative relationship between good corporate governance and financial performance. This shows that the market response to the implementation of good corporate governance is still lacking and the implementation of good corporate governance requires a longer period long time to see its success.